Exploring the History of Islamic Accounting and the Concept of Accountability in an Islamic Perspective - Kautsar Riza Salman (Universitas Muhammadiyah Yogyakarta, 2022)
The history of conventional accounting dominates the literature on the history of accounting, and it is still rare to find a history that describes Islamic accounting comprehensively. In addition, the concept of accountability is still dominated by financial accountability alone. This paper aims to describe the history of Islamic accounting starting from the period of the Prophet until the 20th century. This paper also attempts to describe the concept of accountability from an Islamic perspective. The research approach used in this paper is categorized as qualitative research. The bibliographic method or library analysis used in this study reviews some of the previous literature on the history of Islamic accounting and Islamic accountability. History proves that Muslims have implemented modern and sophisticated accounting systems and practices. The manuscript by Al-Mazindarani entitled